Lemmus trimucronatus Richardson 1825 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lemmus trimucronatus Richardson 1825 Lemmus trimucronatus Richardson 1825, in: Parry, Journal of a second voyage …, App.: 309. Type Locality: Canada, District of Mackenzie, Point Lake. Vernacular Names: Nearctic Brown Lemming. Synonyms: Lemmus alascensis Merriam 1900; Lemmus harroldi Swarth 1931; Lemmus helvolus (Richardson 1828); Lemmus minusculus Osgood 1904; Lemmus nigripes (True 1894); Lemmus phaiocephalus Manning and Macpherson 1958; Lemmus subarticus Bee and Hall 1956; Lemmus yukonensis Merriam 1900. Distribution: N Chukotskiy region in far NE Siberia (coastal region east of Kolyma River, not inland); in North America, from W Alaska east to Baffin Isl and Hudson Bay, and south in the Rocky Mtns to C British Columbia, Canada; also Nunivak and St. George isls in the Bering Sea, Pribilof Isls, and Canadian Archipelago (Jarrell and Fredga, 1993:Fig. 2). Conservation: alascensis Merriam, 1900; harroldi Swarth, 1931; helvolus (Richardson, 1828); minusculus Osgood, 1904; nigripes (True, 1894); phaiocephalus Manning and Macpherson, 1958; subarticus Bee and Hall, 1956; yukonensis Merriam, 1900. Discussion: Rausch (1953) proposed the synonymy of trimucronatus and nigripes under Old World L. sibiricus , a taxonomic arrangement elaborated by Rausch and Rausch (1975 b ) and maintained in subsequent faunal and systematic works (Banfield, 1974; Hall, 1981; Honacki et al., 1982; Jones et al., 1986, 1997; Musser and Carleton, 1993). As now understood, L. trimucronatus is the only true lemming to exhibit a recent transberingian geographic distribution; see Chernyavskii et al. (1993) and Federov et al. (1999 a ), who speculated about Beringian history and possible dispersion pathways for lemmings. North American subspecies revised by Davis (1944) and retained as such by Hall and Cockrum (1953) and Hall and Kelson (1959); North American populations reviewed by Batzli (1999). Corbet and Hill (1991) continued to recognize the St. George Isl form nigripes as a species. Among Eurasian Lemmus , hybridization results (Pokrovski et ...